Knowledge on Premarital Sex and its Consequences Among Adolescents at a Higher Secondary School. - Bhandari, Sushila Devi (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: The premarital sex knowledge and consequences among adolescents was the subject of the research presented. Premarital sex issues are bombarding and it is an emerging topic, though adolescents are not being serious about it, they will be in great trouble in near future if they did not get adequate knowledge about this topic as premarital sex consequences rates are increasing day by day in all over the world like STIs, adolescence pregnancy, guilt, depression, stress, loss of self-respects etc especially on young adolescents. Methods: It was descriptive, cross-sectional study. Simple random sampling lottery method was used for obtaining 141 samples from higher secondary school. Self-administered questionnaire was distributed among adolescent to obtain their responses regarding premarital sex. Results: Out of 141 respondents, the study revealed that 87.2% responded premarital sex to be inappropriate. While 34% responded the cause of having premarital sex is due to lack of sex education. Regarding the consequences of premarital sex majority of the respondents were aware about different consequences that may occur due to premarital sex. Conclusions: Majority of the respondents had knowledge about premarital sex and its consequences. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12999